How “Fast” is Fast Furniture? - Furmston, Katryn; Braithwaite, Naomi (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper explores the emerging concept of fast furniture, a rapidly growing sector characterized by quick production, low costs, and short product life cycles. Despite its substantial environmental impact, fast furniture remains underexplored in academic literature. Drawing parallels to fast fashion in its focus on trends, disposability, and mass production, this study examines the intersections of consumer behaviour, industry practices, and sustainability challenges within the context of fast furniture. Through a mixed-methods approach, combining a quantitative/qualitative survey of UK consumers and interviews with industry professionals, the study reveals significant insights into consumer perceptions, motivations, and the role of fashion-driven consumption in shaping the furniture market. Key findings indicate that while consumers increasingly engage with trend-driven furniture purchases, many are unaware of the term "fast furniture." Moreover, despite their significant market share, brands like IKEA are not strongly associated with the "fast" model by consumers, who instead view their products as affordable and functional, yet temporary. Industry professionals, meanwhile, emphasize that the "fastness" of furniture is determined largely by consumer choices, not necessarily the manufacturing process. This research stems from a larger doctoral study that contributes to the growing body of knowledge on sustainable consumption, advocating for a broader understanding of fast furniture as a consumer-driven phenomenon rather than an industry-defined product category. Future research is suggested to further explore the global dynamics of fast furniture consumption, the role of consumer education, and sustainability initiatives within the industry.